The Test Fungi Growth Physiology of Trichoderma sp. and Gliocladium sp. from Citrus Plants - Unun - Triasih; Sri Widyaningsih (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
One of the problems of citrus cultivation is disease attack which can cause a decrease in production during harvest. There are antagonistic fungi from citrus plants that can be used to control pathogens, namely Gliocladium sp. and Trichoderma sp. Antagonistic fungi will be able to control pathogens optimally if they have growth conditions that match their environment. This study aims to determine the growth development of Trichoderma sp. and Gliocladium sp. at several temperatures, media, exposure lengths, and types of light. The treatments used were four different temperatures (20°C, 25°C, 30°C, 35°C), three media (PDA, PDAY, and CMA), several exposure times (24 hours of light and 24 hours of dark, 8 hours of light and 16 hours of darkness, 16 hours of light and 8 hours of darkness) and the type of light (light from a reading lamp placed very close, light from a lamp placed habitually, and dark wrapped in carbon). The treatment used a completely randomized design (CRD) and was repeated 5 times. The test results showed that the two isolates could develop optimally on PDA and PDAY media with the best temperature of 20°C-25°C. In addition, testing of various rays showed the results of the fastest development by Trichoderma sp. under natural light treatment. Furthermore, the best length exposure test was Trichoderma sp. with a lighting time of 12 hours light and 12 hours dark. In general, the development of the two antagonistic fungal isolates had relatively the same optimal development conditions, but Trichoderma sp. has better development on various tests.